Jangkang Baris Dance in Sidatapa Village Study on The Meaning And Potential as Tourist Attraction - Ida Ayu Trisnawati; Dedi Gusman (Institut Seni Indonesia Denpasar, 2023)
This study aims to determine the meaning and potential as a tourist attraction for the Baris Jangkang Dance in Sidatapa village. This dance is very distinctive with the Balinese Aga culture which is different from Balinese culture in general. This research is qualitative in nature starting with determining the location in Sidatapa village. Collecting data using in-depth interviews, observation, and document studies. The results were analyzed using interactive analysis. The results showed that the Baris Jangkang Dance in Sidatapa village was popularly known as the Jangkang dance or war dance. This dance is used as a representation of the warrior spirit of the Sidatapa community in dealing with enemies who disturb the peace of the village. Baris Jangkang dance dancers are divided into two types of dancers, namely truna dancers (never dance) and surudan dancers (already dancing). Its position is divided into prabangsa (leader) and prawira (troop). The first potential could be watching dance and drum practice. The second is by watching live during the show. Third, selling various documentations of the Baris Jangka dance in various forms, such as VCDs, photos, clothes and as souvenirs for Sidatapa.